2015
DOI: 10.2174/1874192401509010040
|View full text |Cite
|
Sign up to set email alerts
|

Is Vitamin D Deficiency a New Risk Factor for Cardiovascular Disease?

Abstract: The role of vitamin D in the regulation of bone metabolism has been well established. However, in recent years, many studies have demonstrated that its role extends far beyond bone health. Growing evidence has shown a strong association between vitamin D deficiency and hypertension, metabolic syndrome, diabetes mellitus and atherosclerosis. The mechanisms by which vitamin D exerts its cardiovascular protective effects are still not completely understood, but there is evidence that it participates in the regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
2
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 61 publications
0
45
2
7
Order By: Relevance
“…A post mortem examination of a child, who died due to vitamin D deficiency associated cardiomyopathy showed a large pericardial effusion and an enlarged heart with a dilated and concentric hypertrophic left ventricle. There was a mild increase in interstitial fibrous tissue, particularly in the subendocardial regions and the cardiomyocytes were thin and elongated in keeping with dilated cardiomyopathy [14].…”
Section: Heart Diseasementioning
confidence: 85%
See 4 more Smart Citations
“…A post mortem examination of a child, who died due to vitamin D deficiency associated cardiomyopathy showed a large pericardial effusion and an enlarged heart with a dilated and concentric hypertrophic left ventricle. There was a mild increase in interstitial fibrous tissue, particularly in the subendocardial regions and the cardiomyocytes were thin and elongated in keeping with dilated cardiomyopathy [14].…”
Section: Heart Diseasementioning
confidence: 85%
“…In a study among 102 African Americans, vitamin D deficiency was observed in 84-96% of heart failure patients, whereas only one-third of the healthy controls were vitamin D deficient [14]. Two more studies among African Americans also showed a high prevalence of vitamin D deficiency in patients with heart failure.…”
Section: Heart Diseasementioning
confidence: 97%
See 3 more Smart Citations